Imagine that! : how Dr. Seuss wrote The cat in the hat - Sierra, Judy (Random House Children's Books, a division of Penguin Random House LLC, 2017)
Presents an account of the early career of Ted Geisel, otherwise known as Dr. Seuss, describing how he adhered to strict literary guidelines while writing "The Cat in the Hat."